Mobile Application with Arduino to Improve the Determination of the Ripening Status of the Fruit - Cabanillas-Carbonell, Michael; Céspedes-Lluque, Víctor; Yucra-Calla, Miguel; Herrera Salazar, José Luis (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Fruit consumption is related to the enjoyment of good health and the reduction of the occurrence of diseases such as obesity. At present, in the markets the process of determining the state of maturity of fruits is carried out by employees using only their criteria, since this method is very broad and tedious when carried out, for this the present investigation was developed, in improving the process of determining the state of maturity of fruits. The article exposes the development of a mobile application with Arduino, based on Scrum, to improve the determination of the state of maturity of fruits in markets. Resorting to the use of pure experimental design with a sample of 30 data for each indicator. The results indicate that the margin of error when determining the resistances of the fruit with the application with respect to the multimeter was 4.73 percent and in determining the color of the fruit with respect to the sensor was 6.09 percent. It was concluded that the prototype fulfills its function of determining the state of maturity of the fruit by means of these 2 sensors implemented in the Arduino, having a minimum margin of error.